Developing a Conceptual Framework of Buyer-Supplier Relationship Quality in the Supply Chain and Prioritizing its key Components: A Meta-Synthesis Method - Hashem Aghazadeh (University of Tehran, 2020)
Objective: Relationship quality is recognized as the key concept of buyer-supplier relationships in the supply chain. The purpose of this study is to review and analyze the buyer-supplier relationship quality and prioritize its components. Methods: Using a Meta-Synthesis Method, existing research on the buyer-supplier relationship quality from 1998 to the spring of 2020 was collected using relevant search terms. Then, due to the title, inclusion criteria, abstract, exclusion criteria and critical appraisal skills program checklist, irrelevant articles were removed and final articles were selected. By coding and synthesizing the findings of selected articles in MAXQDA, key components and categories of relationship quality were identified. Finally, by using an analytic hierarchy process, the components of relationship quality were prioritized by gathering the opinions of industry and academic experts and using Expert Choice software. Results: According to the research findings, the buyer-supplier relationship quality consists of three dimensions: social, technical and relational. The social dimension includes trust, commitment and satisfaction. The technical dimension consists of cooperation, knowledge management and adaptation, and the relational dimension includes interaction and the nature of the relationship. Conclusion: The results show that trust is the most important component of relationship quality and then, respectively, cooperation, interaction, commitment, satisfaction, knowledge management, adaptation and the nature of the relationship are recognized as the most important components of relationship quality. In order to improve the quality of their relationship and get its benefits, the parties to the relationship should focus on strengthening and upgrading the mentioned components